The Effect of Compensation, Work Environment and Work Motivation on Job Satisfaction at Gojek Partners in Gunung Anyar District - Putra, Riyan Sisiawan; Dhea Feby Risma (GREENOMIKA, 2024)
This study aims to determine the effect of compensation variables, work environment and work motivation on job satisfaction in Gojek drivers. This study uses primary data obtained from distributing questionnaires. This research method uses a quantitative method, the sample used in this study is 95 motorcycle taxi drivers in the Gunung Anyar sub-district, who have met the criteria used in the study. The distribution of the questionnaire was carried out online via the Google form. The analysis in this study uses SPSS (Statistical Program for Social Science) analysis. The results of this study indicate that compensation, work motivation have a significant positive effect on job satisfaction, while the work environment has no significant effect on job satisfaction.